1996
DOI: 10.1007/bf00177703
|View full text |Cite
|
Sign up to set email alerts
|

Role of substance P and neurokinin A in toluene diisocyanate-induced increased airway responsiveness in rabbits

Abstract: The aim of the present study was to examine the role of neuropeptides, especially substance P (SP) and neurokinin A (NKA), in toluene diisocyanate (TDI)-induced airway hyperresponsiveness (AHR) to acetylcholine aerosols. Thirty parts per billion of TDI in air administered over 4 hours caused a significant increase in the airway constrictive response to acetylcholine (ACH) aerosols in rabbits (DeltaRI: 245 +/- 30%, p < 0.005) without altering basic values of respiratory, cardiovascular or blood gas parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…From these results we conclude that MIC and TDI share some properties in terms of respiratory toxicity. Previously it was reported that TDI-induced airway hyperreactivity is dependent on tachykinins [38], suggesting a plausible mechanism for induction of immediate bronchoconstriction by diisocyanates [25, 39, 40]. Moreover, a connection between release of tachykinins, immunoglobulin production, leukocyte recruitment and activation has been established in earlier studies [41, 42], indicating that diisocyanate-induced respiratory toxicity could trigger the subsequent immune response.…”
Section: Discussionmentioning
confidence: 94%
“…From these results we conclude that MIC and TDI share some properties in terms of respiratory toxicity. Previously it was reported that TDI-induced airway hyperreactivity is dependent on tachykinins [38], suggesting a plausible mechanism for induction of immediate bronchoconstriction by diisocyanates [25, 39, 40]. Moreover, a connection between release of tachykinins, immunoglobulin production, leukocyte recruitment and activation has been established in earlier studies [41, 42], indicating that diisocyanate-induced respiratory toxicity could trigger the subsequent immune response.…”
Section: Discussionmentioning
confidence: 94%
“…Hierzu liegen zahlreiche -auch mechanistische -Untersuchungen an Kaninchen und Meerschweinchen sowie in vitro vor, auf die hier nicht näher eingegangen wird. Auf eine Übersichtsarbeit (Raulf-Heimsoth und Baur 1998) und einige neuere Untersuchungen hierzu (Gagniere et al 1996(Gagniere et al , 1997Lastbom et al 1996;Mapp et al 1996;Marek et al 1996) sei verwiesen.…”
Section: Hautunclassified
“…A detailed description of the rabbit model and the statistical data analysis has been presented in previous papers [12,13]. Male and female white New Zealand rabbits of the same breed and of similar age and body weight (3.5-4.0 kg) were anaesthetized with 20-30 mg·kg -1 thiopentobarbital sodium (Trapanal®; Byk Gulden, Konstanz, Germany) after premedication with 25 mg·kg -1 ketamine hydrochloride (Ketanest®; Parke-Davis, Berlin, Germany) and 5 mg· kg -1 xylazin (Rompun®; Bayer, Leverkusen, Germany) and placed in a supine position.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The particles had a diameter of 0.5-5.5 µm. During the challenge tests, animals inhaled for 1 min with a mean of 1.1±0.3 L from the ACh aerosol [12], which corresponded to a total dose of 0.05 and 0.5 mg ACh, respectively (0.2% and 2.0% solution).…”
Section: Airway Hyperresponsiveness In In Vivo Experimentsmentioning
confidence: 99%